Synovial hemangiomas of wrist and ankle joint: A report of two rare cases - Priyanka Saxena; Radhika Agarwal; Gunjan Nain; Nita Khurana; Pawanindra Lal; Sanjeev Kumar Tudu (Wolters Kluwer Medknow Publications, 2018)
Synovial hemangioma is a rare, benign, vascular tumor of synovium leading to joint pain and swelling. The most common site is the knee joint, but rare cases involving other sites have also been reported. We report two rare cases of synovial hemangioma, one involving the ankle joint and other involving the wrist joint. Histopathology is the gold standard for diagnosis of these cases. Early treatment is warranted to prevent the risk of permanent joint damage.